Growth in a Globalised Economy: The Effects of Capital Taxes and Tax Competition - Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2003)
This contribution provides evidence for the hypothesis that trade increases growth through its curbing effect on capital taxes. The analysed mechanism includes two different steps and considers the critical points of both the theoretical and empirical studies in this field. In particular, the estimation problems of omitted variables and parameter heterogeneity are addressed. Using panel data for a sample of 12 OECD countries in the time period 1967-1996, it is shown that the theoretical predictions can be corroborated by empirical results.
Keywords: F43; O40; H71; 330; Trade and Growth; Tax Competition; OECD Countries; Wirtschaftswachstum; Globalisierung; Steuerwettbewerb; Kapitalertragsteuer; Schätzung; OECD-Staaten